Ddx21 mutant peptide is an effective neoantigen in prophylactic lung cancer vaccines and activates long-term anti-tumor immunity - Zhang, Zhe; Xia, Yimeng; Wang, Zhihong; Sun, Yaxing; Pu, Dan; He, Yijia; Liu, Ruixian; Zhang, Yanru; Liu, Yan; Yu, Junzhi; Ning, Shiyang; Feng, Baisui; et al. (Frontiers in Immunology, 2025)
IntroductionLung cancer is the leading cause of cancer-related death worldwide, and its morbidity and mortality are increasing. Although low-dose CT lung cancer screening has been shown to reduce lung cancer mortality, its adoption rate is limited and the pace of its promotion is slow, highlighting the urgent need for more effective prevention measures. Prophylactic vaccines play a crucial role in cancer prevention. Our previous studies indicated that mice immunized with a prophylactic vaccine based on lung cancer cell lines KPL 160302S, derived from early-stage murine lung cancer tissues, exhibited a significantly extended survival period, with a strong anti-tumor immune response. While the vaccine based on KPL 160424S, derived from advanced-stage murine lung cancer tissues, failed to extend survival time and demonstrated limited capacity to stimulate anti-tumor immunity. MethodsTo investigate the fundamental reason for the difference between KPL 160302S and KPL 160424S vaccines, we employed bioinformatics methods and immune related experiments to explore the effects and mechanisms of the screened neoantigens. ResultsOur findings demonstrated that immunization with the Ddx21 mutant peptide (Ddx21MT), unique to KPL 160302S, could significantly increase the proportion of central memory T cells (TCM) in mice and activate anti-tumor immunity. DiscussionThese results suggest that the Ddx21MT is a highly effective neoantigen that can activate anti-tumor immunity, which can serve as an important component in developing a lung cancer vaccine and is expected to be used in combination with other immunotherapy approaches.